The effects of postseason break on stabilometric performance in female volleyball players - Dai, B.; Sorensen, C. J.; Gillette, J. C. (Sports Biomechanics, 2010)
Ankle sprain is a common injury in volleyball. Poor stabilometric performance (SP) is associated with high risks of sustaining ankle sprain. Balance training can improve SP and reduce ankle sprain, but no research has studied the effects of detraining on SP in highly trained athletes. The purpose of this study was to determine the effects of one-month postseason break on SP in female volleyball players. Eleven NCAA female volleyball players participated in two eye-closed single-leg stance tests before and after a one-month postseason break. Stance time, center of pressure (COP) area, COP standard deviation, and COP mean velocity were assessed during the tests. During the postseason break, subjects conducted self-selected exercise and the average training duration was 87% lower compared to the competition season. Subjects demonstrated significant increases in anterioposterior (A/P) COP standard deviation (1.6 ± 0.4 vs. 1.8 ± 0.4 cm, p = 0.05), mediolateral (M/L) COP velocity (6.5 ± 1.5 vs. 7.1 ± 1.3 cm/s, p = 0.05), and overall COP velocity (10.1 ± 2.0 vs. 11.6 ± 1.9 cm/s, p = 0.02) after postseason break. SP decreased in highly trained female volleyball players after one-month postseason break. The decrease in SP indicated a possible increased risk for ankle sprain injury.